Neuronal Damage and Neuroinflammation, a Bridge Between Bacterial Meningitis and Neurodegenerative Diseases - Farmen, Kristine; Tofiño-Vian, Miguel; Iovino, Federico (Frontiers in Cellular Neuroscience, 2021)
Bacterial meningitis is an inflammation of the meninges which cover and protect the brain and the spinal cord. Such inflammation is mostly caused by blood-borne bacteria that cross the blood-brain barrier (BBB) and finally invade the brain parenchyma. Pathogens such as Streptococcus pneumoniae, Neisseria meningitidis and Haemophilus influenzae are the main etiological causes of bacterial meningitis. After trafficking across the BBB, bacterial pathogens in the brain interact with neurons, the fundamental units of Central Nervous System, and other types of glial cells. Although the specific molecular mechanism behind the interaction between such pathogens with neurons is still under investigation, it is clear that bacterial interaction with neurons and neuroinflammatory responses within the brain leads to neuronal cell death. Furthermore, clinical studies have shown indications of meningitis-caused dementia; and a variety of neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease and Huntington's disease are characterized by the loss of neurons, which, unlike many other eukaryotic cells, once dead or damaged they are seldom replaced. The aim of this review is to provide an overview of the knowledge on how bacterial pathogens in the brain damage neurons through direct and indirect interactions, and how the neuronal damage caused by bacterial pathogens can, in the long term, influence the onset of neurodegenerative disorders.